The Ability of Senior High School Student to Propose Linear Equations Systems of Two Variables Problem - Rachmawati, Yemima Indah; Sugandi, Eko; Prayitno, Lydia Lia ((JRAMathEdu) Journal of Research and Advances in Mathematics Education, 2018)
The purpose of this research is to describe the ability of senior high school student in proposing LESTV problem. This research is quantitative descriptive research. The data collecting used in this research is through proposing problem in the area of LESTV material. The subjects participating in this research are 60 students of senior high school in the Surabaya Eastern. Based on the problem proposed by the students then it is classified into three groups namely, mathematical question, non-mathematical question, or statement. If the problem proposed is mathematical question, the analysis will be done by grouping the problem into the problem can be solved or can not be solved. Then, the problem can be solved will be classified based on the structure of syntax and semantics. The results show that in proposing the problem the subjects mostly can solve the problem, in proposing the problem tends to add new information and relevant to the problem. Based on the structure of semantics, it is found that the students can restate, classify, and compare and also modify the problem from information provided. Meanwhile, in terms of the structure of semantics, the students can propose the problem contains assignment, comparison, and use of additional information (new information). Keywords: Proposing problem; SPLDV; Syntax; Semantics.